Cinnamon Protects Kidneys Against Doxorubicin-Induced Nephrotoxicity - Gurel, Ali; Aydin, Hasan; Yalcin, Alper; Yilmaz, Erkan; Turk, Ahmet; Metin, Tuba Ozcan; Keles, Hikmet (Sci Printers & Publ Inc, 2022)
OBJECTIVE: Doxorubicin (DOX), an anthracycline antibiotic, is a potent and indispensable chemotherapeutic drug that has adverse outcomes associated with it, such as nephrotoxicity. Cinnamon, however, is a strong free radical scavenger antioxidant against oxidative stress-associated pathologies. The current study aims to investigate the protective effects of antioxidant compounds of cinnamon spice on DOX-induced nephropathy (DIN). STUDY DESIGN: Male albino Wistar rats were divided into 5 groups (n = 6 each) as control (no treatment was performed), sham (olive oil for 14 days 1 mL/kg by oral gavage), cinnamon bark oil (CO) (100 mg/kg cinnamon dissolved in olive oil and given by oral gavage for 14 days), DOX (10 mg/kg, a single dose was given intraperitoneally on the eighth day), and DOX + CO groups. Histopathological, electron microscopic, immunohistochemical, and biochemical analyses were performed on the liver tissues of the rats. RESULTS: The results of light and electron microscopy analysis showed severe kidney tissue damage after DOX treatment. Significantly increased transient receptor potential melastatin 2 (TRPM2) expression, tissue malondialdehyde (MDA) levels, and decreased catalase (CAT) enzyme activity were observed due to DOX. Biochemical, histopathological, and immunohistochemical examinations revealed that concomitant cinnamon administration together with DOX significantly reversed DIN. CONCLUSION: Our data suggests that cinnamon has histological, immunohistochemical, and biochemical protective effects on DOX-induced nephropathy.
Keywords: cinnamon; doxorubicin; kidney; nephrotoxicity; oxidative stress; transient receptor potential channels; TRPM cation channels